Histopathological Effects of Cadmium Chloride on Barbus sharpeyi - M.Salman, Noor; J. Al-Rudainy, AbdAlmotalib; B. Faleh, Anaam (Iraqi Journal of Science, 2023)
The present study including determined pathological changes in Barbus sharpeyi, aswell as description behavior and growth of bunni fish by used 180 fingerlings, Fishwere distributed randomly upon four treatments in addition to control group. Firsttreatment (T1) contained cadmium 0.093mg/L with changing water and added cadmiumcontinuously, the second treatment (T2) contained cadmium 0.093mg/L with changingwater without adding cadmium, third treatment (T3) contained cadmium 0.046mg/Lwith changing water and adding cadmium continuously, fourth treatment (T4) containedcadmium 0.046mg/L with changing water without adding cadmium. In order to estimateLC50 used 120 fingerlings of fish B. sharpeyi, were exposed to 0.5, 0.6, 0.7, 0.8, 0.9and 1.0mg/L. The LC50 of cadmium was 0.932mg/L for 48h of exposure. Fish behaviorwas recorded showed abnormalities after exposure to the various cadmiumconcentrations such as swimming disorders, the fish tended together at the surface, fastmovement, fish aggregate in aquarium border, fish weakness, opened and closed inoperculum festally, as well as a significant decrease at (P≤0.05) in body weight ofT1,T2 and T3. Histopathological changes in gills characterized by lamellar fusion,lifting of secondary lamella, The main findings in liver tissue were hydropic swellingand fatty degeneration of some hepatocytes, focal or diffuse necrosis, Kidney resultvarying degrees of tubular necrosis with severe congestion together withmelanomacrophage infiltration. Intestine results showed slauphing and necrosis ofmucosal epithelial of intestinal villi and diffuse MNCs infiltration, hyperplasia andhypertrophy of goblet cell. Spleen observed severe destruction in spleenic parenchyma,severe reduction in hemopoitic tissue.